Factors Affecting the HbA1c among Older Adults with Type 2 Diabetes Mellitus in Muang District Mahasarakham Province - suriya, natthawut; Deeprom, Keskanok; Teemueagsa, Wisaruta; Chaithawatwibun, Aranya; karunan, kholid (Princess of Naradhiwas University Journal, 2025)
This cross-sectional descriptive study aimed to explore the factors influencing HbA1c level among older adults with type 2 diabetes. A sample of 230 individuals was systematically selected. The content validity of the questionnaires was certified by three experts resulting in an Item-Objective Congruence (IOC) score of the self-management behavior questionnaire related to diabetes and the social support was between 0.67-1.00. The Cronbach's alpha coefficient for the self-management behavior questionnaire related to diabetes was 0.83, and the social support was 0.89. The statistical analyzes were descriptive statistic, pearson’s correlation coefficient and multiple linear regression. The results indicated the majority of the sample were females (75.65%), with 66.96% reporting a married status and 88.70% were graduated primary school. Moreover, 63.47% were identified with overweight conditions, while 62.61% of the sample could not control their HbA1c levels. Factors including body mass index (r =.64, p < .05), duration of disease (r = .45, p < .05), self-care behaviors (r = .86, p < .05), and social support (r = .68, p < .05) were positively correlational influence the HbA1c levels, predicting 33% of the variance (R2 adjust= 33, p < .005). Conclusion, promoting self-care behaviors including consuming nutritious food, maintaining appropriate weight, and receiving support from family members and healthcare professionals could effectively empower older adults with diabetes to control HbA1c efficiently.